2019
DOI: 10.1161/circresaha.118.314191
|View full text |Cite
|
Sign up to set email alerts
|

Application of PCSK9 Inhibitors in Practice

Abstract: Protein convertase subtilisin/kexin type 9 (PCSK9) inhibitors (PCSK9i) are set to revolutionize the treatment of hypercholesterolemia in the management of atherosclerotic risk, but numerous reports have detailed unprecedented barriers to access for these drugs. To overcome these challenges, our group created a model to facilitate provision of this new therapy for patients who qualify according to FDA criteria. This report details the real-world follow-up experience of PCSK9i use in a large patient cohort struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 22 publications
3
45
0
3
Order By: Relevance
“…The most common adverse events include myalgia, myositis with increased creatine phosphokinase (CPK), and rhabdomyolysis in very few cases. Myalgias are not considered significant as long as they do not increase CPK or cause myositis or rabdomyolysis [44]. If the striated muscle hurts it is because it is affected, but how it is affected is still unknown.…”
Section: Evolution Of Knowledgementioning
confidence: 99%
“…The most common adverse events include myalgia, myositis with increased creatine phosphokinase (CPK), and rhabdomyolysis in very few cases. Myalgias are not considered significant as long as they do not increase CPK or cause myositis or rabdomyolysis [44]. If the striated muscle hurts it is because it is affected, but how it is affected is still unknown.…”
Section: Evolution Of Knowledgementioning
confidence: 99%
“…[1][2][3][4] Recently published real-world studies indicate that 42.9-67.0% of patients are statin intolerant before receiving PCSK9 inhibitor monoclonal antibody therapy, thereby emphasizing statin intolerance as an important realworld therapeutic challenge. [5][6][7][8] In the 24-week, randomized, double-blind ODYSSEY ALTERNATIVE study (NCT01709513), the PCSK9 inhibitor alirocumab 75 mg administered every 2 weeks (Q2W; with possible dose adjustment to 150 mg Q2W) reduced low-density lipoprotein cholesterol (LDL-C) by 45.0% vs 14.6% with ezetimibe in patients with primary hypercholesterolemia who were intolerant to statins, defined as the inability to tolerate $2 statins, including 1 at the lowest-approved starting dose, due to muscle symptoms. 9 All patients who had successfully completed the double-blind treatment period (DBTP) were eligible to enter an optional open-label treatment period (OLTP).…”
Section: Introductionmentioning
confidence: 99%
“…The ODYSSEY trial showed that PCSK9 inhibitors are effective either when used alone or in combination with other lipid-lowering agents, while the FOURIER trial showed that PCSK9 inhibitors were effective on a background of statin therapy [ 3 , 5 ]. A 30 mg/dL drop in LDL-C, or a 59% reduction from LDL-C baseline, was revealed by the FOURIER trial when PCSK9 inhibitors were added to statin therapy [ 6 ]. A common indication for monotherapy with PCSK9 inhibitors is statin intolerance.…”
Section: Discussionmentioning
confidence: 99%